2010
DOI: 10.1186/1749-799x-5-64
|View full text |Cite
|
Sign up to set email alerts
|

Lessons to be learned from a missed case of Hamate fracture: a case report

Abstract: IntroductionWe report the case of a missed fracture through the body of the hamate bone, only detected on a later, mistakenly taken 30° oblique x-ray view. This case highlights some of the problems encountered with traditional x-ray views, and the need to consider oblique views as either standard procedure or as an adjunct where clinical suspicion remains high even in the presence of normal x-rays.Case presentationA healthy 26-year-old Caucasian male fell whilst jogging, suffering a low velocity injury to his … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 8 publications
0
8
0
3
Order By: Relevance
“…Hamate fractures are frequently missed at the time of presentation because of paucity of signs and symptoms, relative rareness of the injury pattern, and complex carpal anatomy [3,4,9,10]. Ebraheim et al reported a mean delay of 10 days for the diagnosis from the time of injury [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hamate fractures are frequently missed at the time of presentation because of paucity of signs and symptoms, relative rareness of the injury pattern, and complex carpal anatomy [3,4,9,10]. Ebraheim et al reported a mean delay of 10 days for the diagnosis from the time of injury [4].…”
Section: Discussionmentioning
confidence: 99%
“…Ebraheim et al reported a mean delay of 10 days for the diagnosis from the time of injury [4]. The importance of oblique views of wrist and high resolution CT for early diagnosis has been stressed in the literature [9,11].…”
Section: Discussionmentioning
confidence: 99%
“…Les fractures de type II sont moins courantes [5]. Celles de type I sont liées le plus souvent au sport de raquettes et de bâtons (tennis, golf.…”
Section: Discussionunclassified
“…Le diagnostic est essentiellement radiologique reposant sur des clichés de face, de profil, et surtout des incidences obliques à 30-45 • [5]. La TDM reste l'examen de choix dans le diagnostic de ce type de fracture en précisant les traits fracturaires et le nombre de fragments ainsi que leur possible déplacement [2].…”
Section: Discussionunclassified
See 1 more Smart Citation